(untitled) (Herald of the National Children’s Medical Center, 2025)
Background. We have examined and compared the results of the articles on LEVUR and TVUR in this systematic review and meta-analysis. Materials and methods. To find all the studies about TVUR and LEVUR in the pediatric population, we examined the databases. Exclusions were review articles, unfinished articles, duplicate publica- tions, and robot-assisted publications. To determine patient information, reflux grades, laterality, length of operation, time to discharge, success rate, and complications, a systematic review was carried out. Results. 23 articles -13 on TVUR and 10 on LEVUR - were included after a total of 45 articles were screened. In TVUR grade 5 VUR was substantially larger (11.9%, p = 0.001) than in LEVUR (2.2%). When comparing TVUR to LEVUR, the percentage of bilateral reimplantation was considerably higher (p = 0.001). 96.7% was the success rate of LEVUR, a considerable increase above TVUR 93.7% (p = 0.007). Unilateral/bilateral TVUR took significantly longer duration of surgery (155/194 min vs 107/161 min) compared to LEVUR (p = 0.001). The mean (s.d) time to discharge was longer at 3.2 (1.6) days for TVUR compared to 1.6 (0.4) days for LEVUR (p = 0.001). The complication rate was comparable, 7.35% for TVUR and 5.35% for LEVUR (p = 0.167). Conclusion. With regard to success rates and side effects, LEVUR and TVUR appear to be reason- able substitutes for open ureteric reimplantation. Compared to TVUR, which was recommended for bilateral UR and grade 5 VUR patients, LEVUR was more preferable for unilateral, grades 1-4 cases, had higher success, and required a shorter hospital stay. Although the types of complications varied according to the procedure, there was no discernible difference in the complication rate between LEVUR and TVUR.